Potential exposure of children to environmental microorganisms in indoor healthcare and educational settings. Issue 3 (May 2014) - D'Arcy, N.; Cloutman-Green, E.; Lai, K. M.; Margaritis, D.; Klein, N.; Spratt, D. A.
Surveillance of environmental bacteria was performed in order to investigate the differences in number, identity and distribution in three indoor locations where children spend time; a hospital ward, outpatient's area and a classroom. Surface total viable counts (TVCs) and swabs for molecular analysis of bacteria present were taken at each location. TVCs were higher in the classroom and outpatient area than on the ward and on items that were located in physically higher positions. High touch sites had lower bacterial counts. Sequence and biochemical data showed the presence of potential pathogens at all locations. The bacterial profile of the three locations was different and may reflect the functional use of the space and the people who use that space.